PENGARUH TATA KELOLA YANG BAIK TERHADAP MAQOSHID INDEKS PADA BANK SYARIAH - Irman Firmansyah (JURNAL AKUNTANSI, 2018)
This study aims to analyze the performance of each Islamic bank through the maqoshid syariah index approach, which is a measure of performance in accordance with the operational objectives of Islamic banks. In addition, an important factor in producing performance is the application of good governance so that the effect of good corporate governance will be tested on the performance of maqoshid sharia. This research was conducted at Islamic commercial banks in Indonesia in the period 2012 to 2016. The results showed that overall, the bank that has the best Islamic Maqoshid performance is Bank Panin Syariah. Regression analysis results show that good corporate governance does not affect the performance of Islamic banks in Islamic banks in Indonesia. This research proves that good governance in Islamic banks has not been able to improve the performance of Islamic Maqoshid. The biggest possibility is that banks still prioritize profits as a measure of performance.